The Effect of the Social Class on Learning English by the Students of the Department of English, College of Education for Women, Al-Iraqia University - Adil Abdulameer, T.A Suhair (Journal of College of Education, 2020)
This research tackles the role of the social class in learning English language by the students of the department of English, College of Education for Women –Al Iraqia University. It aims at:Identifying the concept of the social class and its types.Knowing the effects of the social classes on learning English language by these students.The data of the application side of the study was taken from the students' answers to the test and the questionnaire that have been made to determine students' social class and its effect on their learning of English language.The procedures followed in this study included a comprehensive test of English language for 50 students from the Department of English College of Education for Women –Al Iraqia University annexed by a questionnaire to determine the social class each student belongs to.The findings showed that most of the students examined have failed in the exam and most of them belong to the low social class. Even those who passed the exam got weak grades. This indicates that low social class has a negative effect on students' level of learning English language, and vise versa.